KERJASMA INDOENSIA DAN AMERIKA SERIKAT TERKAIT PENERAPAN FOREIGN ACCOUNT TAX COMPLIANCE ACT (FATCA) - Kasmi, Nurita; Nizmi, Yusnarida Eka (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This Research describes is an international study that examines the political economy of the US policy-related tax rules known as the Foreign Account Tax Compliance Act (FATCA) and how the cooperation between Indonesia and the United States in implementing this policy. Foreign Account Tax Compliance Act. Foreign Account Tax Compliance Act (FATCA) is a new provision that is set by the Government of the United States are included in the Hiring Incentives to Restore Employment Act passed on March 18, 2010 and entered into force in July 2014. The main objective of the establishment of FATCA is to tackle tax evasion (tax avoidance) by United States citizens who do direct investment through financial institutions abroad or indirect investment through ownership of overseas companies. FATCA requires that foreign financial institutions to report to the Internal Revenue Service on financial accounts held by US Taxpayer owned or foreign institutions where the US taxpayer has a substantial ownership. Formal agreement between Indonesia and the United States about the implementation of the Foreign Account Tax Compliance Act (FATCA) was conducted on May 1, 2014, the Government chose to use the model IGA in implementationFATCA in Indonesia, namely the reporting of financial institutions to the IRS.Keywords : Tax, National Intererst, Investment.